Silencing of ARL14 Gene Induces Lung Adenocarcinoma Cells to a Dormant State - Guo, Fei; Yuan, Dexiao; Zhang, Junling; Zhang, Hang; Wang, Chen; Zhu, Lin; Zhang, Jianghong; Pan, Yan; Shao, Chunlin (Frontiers in Cell and Developmental Biology, 2019)
Recently, a growing number of ADP ribosylation factor (ARF) family members has been suggested to be critical in tumorigenesis. However, the effects of most ARF members on lung adenocarcinoma pathogenesis are still not well disclosed yet. In this study, ARF-like GTPase 14 (ARL14) was screened as an important prognostic factor of lung adenocarcinoma from The Cancer Genome Atlas (TCGA) database and validated by our in vitro experiments. It was found that silencing of ARL14 gene inhibited cell proliferation and the abilities of cell migration and invasion, and it also attenuated radiation damage of lung adenocarcinoma cells but had no effect on the proliferation of normal lung cells. Notably, ARL14 siRNA blocked the extracellular signal-regulated kinase (ERK)/p38 signaling pathway and induced cell cycle arrest in G0 phase, ultimately leading to cell dormancy. Moreover, ARL14 siRNA enhanced the expression of cell death activator DFFA-like effector (CIDEC) that had opposite roles in cell proliferation and migration to ALR14. Collectively, our results suggest that ARL14 has an important role in the pathogenesis of lung adenocarcinoma through CIDEC/ERK/p38 signaling pathway, and thus it could be applied as a new candidate of prognosis indicator and/or therapeutic target of lung adenocarcinoma.